Modeling wireless links for transport protocols. - Gurtov, Andrei
Wireless links have intrinsic characteristics that affect the performance of transport protocols; these include variable bandwidth, corruption, channel allocation delays, and asymmetry. In this paper we review simulation models for cellular, WLAN and satellite links used in the design of transport protocols, and consider the interplay between wireless links and transport. We argue that the design and evaluation of transport protocols can be improved by providing easily available models of wireless links that strike a balance between realism, generality, and detail.There is an ongoing tussle between wireless link design and transport protocol design, with papers about how wireless link designers should take into account the dynamics of TCP, and other papers about how TCP and other transport protocols can be designed or modified for better performance over current wireless link technologies. In this paper we consider how appropriate models for wireless links can help in this tussle, and in the general design and evaluation of transport protocols over wireless links.